The Practice of Drama Games in the 2nd Cycle of Basic Education in a Cape Verde School / A Prática do Jogo Teatral no 2.º Ciclo do Ensino Básico Obrigatório numa Escola em Cabo Verde - Alcinda Andrade; Adalgisa Pontes (Revista Portuguesa de Educação Artística, 2019)
This article reflects on the problem of the discipline of Artistic Education in Basic Education in a school located in the city of Praia, Cape Verde. It aims to contribute to know and analyze the practice of the Drama Games. In this way, the practices and conceptions of the teachers of the 2nd cycle in the 7th grade regarding the Drama Game were studied and the type of articulation that the teachers establish between the Dramatic Expression / Drama Game and the other curricular areas was identified. The results refer to the need to work the discipline of Dramatic Expression and to deepen the relevance of the Drama Games in the educational context and its contribution to the integral, harmonious and solidary development of the individual. / O presente artigo reflete sobre a problemática da disciplina da Educação Artística (EA) no Ensino Básico Obrigatório (EBO) numa escola situada na cidade da Praia, Cabo Verde. Tem como objetivo contribuir para conhecer e analisar a prática dos Jogos Teatrais. Deste modo e recorrendo à metodologia de cariz qualitativa, foram estudadas as práticas e as conceções dos professores do 2.º ciclo (EBO) no 7.º ano de escolaridade, relativamente o Jogo Teatral (JT) e identificadas o tipo de articulação que os professores estabelecem entre a Expressão Dramática/Jogo Teatral e as outras áreas curriculares. Os resultados referem a necessidade trabalhar a disciplina da Expressão Dramática e de aprofundar sobre a pertinência dos Jogos Teatrais no contexto educativo e a sua contribuição para o desenvolvimento integral, harmonioso e solidário do indivíduo.